Comparison of environmental impact assessment of highways in Malaysia, South Africa, Thailand, and Denmark - Stierdahl, Jens; Schroll, Henning (Malaysian Journal of Science, 2004)
he objectives of doing comparative analyses of EIA systems in Malaysia, South Africa, 1 hailand and Denmark are to inform policy makers with a view to improve EIA in the home countries, extend knowledge oi methodological procedures and to increase international understanding of en\ ironmcnial problems. The EIA procedures are aiming to provide individual approvals of different projects and assess and mitigate the potential environmental impacts. Some procedures are written in the EIA legislation but EIA administration and procedures are also based on the national tradition. To overcome this an EIA on a highway was analysed in each of the four countries. In the paper we compare the EIA systems in the four countries across four different themes: Relation to standard EIA procedure, EIA system and surrounding environmental regulation, form of public participation, and scope of and methods in the analyses of environmental impacts. Important findings are; that a participation in international cm ironmcnial conventions is reflected in the EIA issues, EIA will expand on issues where environmental legislation is considered insufficient, cultural determined issues will be enclosed in the EIA. and public access and public participation in the decision process are present in all four countries but in very different ways